ANALYZING NEEDS OF ONLINE-BASED EFL ACADEMIC WRITING COURSE: STUDENTS’ VOICES IN COURSE DESIGN - Hanna Sundari (Universitas Indraprasta PGRI, 2022)
Need analysis is a process of collecting information about the needs of teaching and making decisions about the course. This paper reported the learners’ needs on online-based EFL academic writing course during emergency remote teaching. The needs covered two dimensions: present situation analysis and learning situation analysis. The participants were the students who registered for the Academic Writing academic year 2020/2021. The information was collected through a writing test and online questionnaires taken in the initial meetings of the course. The findings showed that the student-participants were heterogeneous in educational background and academic experiences. They found themselves as high-motivated, independent learners with fairly confident writing skill. They confirmed an agreement to the learning objectives to write academic essays and research articles. They revealed that video conferencing and learning management systems were selected for facilitating learning. Moreover, individual work activity using text analysis and essay development was more preferable as learning activities and type of assessment. Students’ sample texts indicated that their writing was sufficient in content and organization though some inaccuracies occurred in grammar, vocabulary, and mechanics. These present and learning situations found on need analysis can be considerations in making decisions of teaching system